2022
DOI: 10.1021/acsnano.2c04831
|View full text |Cite
|
Sign up to set email alerts
|

A Preparative Mass Spectrometer to Deposit Intact Large Native Protein Complexes

Abstract: Electrospray ion-beam deposition (ES-IBD) is a versatile tool to study the structure and reactivity of molecules from small metal clusters to large protein assemblies. It brings molecules gently into the gas phase, where they can be accurately manipulated and purified, followed by controlled deposition onto various substrates. In combination with imaging techniques, direct structural information on well-defined molecules can be obtained, which is essential to test and interpret results from indirect mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…The total energy distribution of the ion beam has a full width at half maximum of 1 eV per charge. 34 Thus, most proteins land with an energy in the range from 1.5 to 2.5 eV per charge. We do not see any distribution in particle quality corresponding to this deposition energy range, but cannot exclude that even lower deposition energies are required to increase sample quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total energy distribution of the ion beam has a full width at half maximum of 1 eV per charge. 34 Thus, most proteins land with an energy in the range from 1.5 to 2.5 eV per charge. We do not see any distribution in particle quality corresponding to this deposition energy range, but cannot exclude that even lower deposition energies are required to increase sample quality.…”
Section: Resultsmentioning
confidence: 99%
“…1 and described in detail elsewhere. 33,34 Protein solutions were prepared using a standard native MS workflow described below. Protein assemblies were transferred into the gas phase via native electrospray ionization using gold coated borosilicate capillaries, prepared in house.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For several decades, practitioners of mass spectrometry (MS) have sought to use MS as a preparative tool. Early works by Robinson et al demonstrated the potential to land protein complex cations onto transmission electron microscopy (TEM) grids for imaging after negative staining. However, the negatively stained images lacked detail, and it is therefore difficult to judge how well the underlying structures were preserved. , More recent work by Rauschenbach et al directly imaged protein complex ions without staining, soft landing them at room temperature and imaging at liquid nitrogen temperature. In those experiments, however, class averaging and 3D reconstruction of the landed protein complexes demonstrated no internal detail suggesting the structures have been perturbed in some way.…”
Section: Introductionmentioning
confidence: 99%